Estudo comparativo dos sistemas construtivos na construção de habitações de interesse social rural Aspectos energéticos e econômicos - Frigo, Juliana Pires (2014)
Several aspects related to dwelling, wellness and life quality demand specific constructive solutions. Considering that the building is one of the responsible by the environment damages because of the quantity of waste, it is also responsible by the electricity waste from the substance extraction to its final product. This study shows a comparative among five combinations of locks and coatings, like: ceramic bricks (plastered), concrete block (plastered), cured lightweight (painted), soil cement (plastered) and soil cement brick with exposed complement (painted), with the purpose to identify which solution is more adequate considering the lowest cost and less electricity spent involved in its process. The adopted methodological procedure is an exploratory research with an explicative approach that enabled the knowledge about the adopted technologies to the rural dwellings study. This study enabled the inputs classification and comparative, executions and spending, having as the mainly result the more viable technology to the rural dwelling and deserve more attention and incentive while its use in a major scale is the soil cement brick with exposed complement only with waterproofing paint related to the spending and electricity economy involved in the execution and use process.